Breastfeeding Practices among Mothers at Birth and at 6 Months in Urban Areas of Delhi-Ncr, India - Mehlawat, Urvashi; Puri, Seema; Rekhi, Tejmeet Kaur (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
The objective of the present was to potray the breastfeeding practices followed by breastfeeding mothers, at birth and at 6 months, in urban areas of Delhi-National Capital Region. For this, 185 dyads of motherinfant aged 6 months were selected from Pediatric Outpatient Department of a government and a private hospital. A questionnaire-cum-interview was designed to collect the participants’ information on breastfeeding practices. It was found that only 29.7% infants had early initiation of breastfeeding despite the high (78.9%) institutional deliveries. Around 40.5% infants were given feeds apart from breast milk, mainly infant formula (81.3%) at the hospital after birth. There were 13% infants who received pre-lacteal feeds, mainly as a traditional family custom. The practice of exclusive breastfeeding for first six months was followed by 62.2% mothers. Complementary feeding or top feeding was received by 71.9% infants, but only 45.1% mothers initiated complementary foods at the recommended age of 6 months. It can be concluded that in the urban areas of India breastfeeding practices remains poor even after rigorous work done for promotion and protection of breastfeeding. Hence strong institutional care and support for breastfeeding is required at birth and efficient counseling for appropriate feeding of the infant is needed to intensify breastfeeding.